A 20-sec Stepping Test and KINECTTM Sensor Provides Objective Quantification of Movement/Balance Dysfunction in Older Individuals. Issue 3 (26th May 2020) - Takeshima, Nobuo; Kohama, Takeshi; Kusunoki, Masanobu; Okada, Sochi; Fujita, Eiji; Oba, Yukiya; Brechue, William F.
ABSTRACT: Background : Tests such as the Functional Independence Measure (FIM) are widely used measures of infirmity and burden of care. However, these scales are largely qualitative and especially problematic when assessing movement-based tasks. Effective, reliable analysis of human movement is technically complicated and expensive, but an infrared depth sensor is potentially a low-cost, portable devise which may provide a quantitative aspect to clinical testing. Our purpose was to assess the utility of a 20-sec stepping test (ST) and Kinect TM infrared-depth sensor in providing objective evaluation of balance toward identifying disability in older adults. Methods : Men and women between 64 and 90 years of age, consisting of independent (IG; n = 37) and dependent (DG; n = 38) living at community, geriatric day-care center in Japan. Total movement distance (TMD) and greatest displacement (MMD) were calculated from Kinect TM recording of the ST. Results : DG had lower FIM scores than IG. TMD and MMD were significantly greater in DG than IG, while step number and rate were lower in DG. Receiver-operator characteristic analysis showed TMD, TMD/step, MMDstep, and MMD corrected for time and height strongly discriminated between assignment to DG or IG with moderate sensitivity and specificity. Conclusions : Greater TMD and MMD observed during a 20-sec ST appear to indicate disability with moderate sensitivity and specificity in older adults. Measures of movement distance (e.g. TMD, MMD) appear indicative of changes in dynamic balance due to a circuitous movement pattern generated by aberrant step replacement with repeated stepping-in-place.